The Climate Security and Energy (Transition) Nexus: Winds of Change - Bößner, Stefan; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Global climate change will likely add pressure to international, national and sub-national security due to its nature as a threat multiplier. The energy system is at the heart of this challenge. On the one hand, two thirds of global emissions come from burning fossil fuels. On the other hand, energy – in particular fossil fuels – have been in the past highly geopolitically influential. But global energy systems are changing. Will this global transition away from fossil fuels to renewables present an opportunity to build peace, or will it instead work to further undermine peace and security worldwide? Energy transitions present a formidable opportunity not only to decarbonize our economies, but also to build a more equitable and decentralized energy system. However, if deployed improperly, and without consideration of the needs of communities, renewable energies might end up repeating past mistakes of the fossil fuel energy regime. Energy transitions harbor both risks and uncertainties when it comes to peace and stability, but with the proper policies in place and research, renewable energies can be made a global success, both in mitigating the worst impacts of the climate crisis and in contributing to peace and stability worldwide.